Carbon Stocks in the Conservation Area of PT. Pertamina (Persero) Fuel Terminal Boyolali - Sunarno Sunarno; Rully Rahadian; Sri Widodo Agung Suedy; Bayu Pradika; Bima Adistya (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2022)
Flora biodiversity has been known to have a vital function in reducing carbon emissions in the air and contributing oxygen in significant levels to the environment. PT. Pertamina (Persero) Fuel Terminal Boyolali (FTB) has an important role in the conservation programs, protection of flora biodiversity, and environmental management. This study aims to analyze carbon stocks found in trees, plants cover soil, litter, necromas, and carbon in the soil and evaluate conservation of flora. This study uses a purposive random sampling method of carbon sources followed by the determination of carbon stocks in three conservation areas managed by PT. FTB, namely in the Wonopotro Forest, in the Pepe River watershed, and Pertamina's operational area. The samples from carbon sources include trees, litter, ground cover plants, necromas, and soil. The trees and necromas carbon sources sampling at each location was carried out at 2 stations with a size of 10 x 50 m2. Meanwhile, the sampling of litter, ground cover plants, and soil was carried out at 2 stations, each consisting of 3 plots. The results showed that the total carbon stock in the conservation areas was 1,688,0791 tons. The Pepe River watershed has the highest total carbon stock, which was 1,466,0928 tons/ha. The FTB and Wonopotro Forest, respectively, have about 180.7569 and 41.2294 tons/ha. The novelty of this research is the method of calculating carbon stocks in a conservation area that can be used as a database for assessing environmental management performance to the preservation of biological resources.